A Rare Primary intramuscular hydatid cyst misdiagnosed as malignant spindle cell tumor: A Case Report (Bangladesh Journal of Medical Science, 2016)
Primary hydatid disease of musculoskeletal system is rare. A 46 year old man presented with soft swelling in anterior aspect of thigh of two years duration which was gradually increasing in size. He was initially diagnosed as malignant spindle cell tumor of thigh, but ultrasonography and Commuted Tomography Scan revealed to be a cystic swelling suggestive of hydatid disease. Our patient had not been operated for hydatid disease previously and investigations did not reveal any hydatid cyst in liver, lung or spleen. So our patient was diagnosed having primary hydatid disease of musculoskeletal system. Serologic test (ELISA) was negative. Patient was given albendazole preoperatively. A careful management is required to prevent systemic dissemination and anaphylactic shock. The swelling was removed en bloc without causing damage to cyst wall and advised for adjunctive albendazole chemotherapy (15 mg/kg/day) for three months.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.628-630